Recommended fluid intake and evidence-based medicine - Šafka, Václav; Fajfrová, Jana; Pavlík, Vladimír; Kučera, Otto; Hůlek, Petr; Horáček, Jan M (Casopis lekaru ceskych, 2019)
Abundant drinking of fluids at any occasion became popular in wealthy society in last decades. It is referred to asserted beneficial health effects, but rationale of these recommendations is disputed in expert environment as hardly traceable and tenable. Authors of the article analyse theoretical issues as well as empiric literary evidence for the current popular recommendation. They find them unfounded and difficult to be defended and the risks of transitive hypo-hydration overestimated. Moreover, they alert true risks of water poisoning we meet not quite rarely in common practice.
Keywords: vodní a elektrolytová rovnováha; medicína založená na důkazech; Water-Electrolyte Imbalance; drinking behaviour; pití; Drinking; Water-Electrolyte Balance; Dehydration; Humans; vodní a elektrolytová nerovnováha; hyponatremia; lidé; recommended daily allowance; dehydration; Evidence-Based Medicine; dehydratace; water-electrolyte imbalance; body water